Preparation and Characterization of Bimetallic Catalyst (NiO – CoO) for Desulfurization of Gas Oil (Baghdad Science Journal, 2016)
In this study NiO - CoO bimetallic catalysts are prepared with two Ni/Co ratios (70:30 and 80: 20) using the precipitation method of nitrate salts. The effects of Ni /Co ratio and preparation methods on the catalyst are analyzed by using different characterization techniques, i.e. atomic absorption (AA) , XRD, surface area and pore volume measurements according to the BET method . The results indicate that the best catalyst is the one containing the percentage of Ni :Co ( 70 : 30 ). Experiments indicate that the optimal conditions to prepare catalyst are stirring for three hours at a temperature of 60oC of the preparation , pH= (8-9) , calcination temperature at 400oC for two hours using the impregnation method . The catalyst activity is studied through the application in the process of oxidative desulfurization of gas oil fuel . The optimal conditions for deep oxidative desulfurization processes are : catalysts 3% , 2 gm. Na2 CO3 , refluxe time 3 hours at 400 C , using a mechanical stirrer at moderate speed (700 rpm), the volume ratio of gas oil : H2O2 : acetic acid is 10: 1: 0.5 and extracted with 1:1 ratio of acetonitrile to the gas oil for three times . The results indicate that the catalysts are efficient to remove sulfur from gas oil depending on temperature, time, concentration of hydrogen peroxide H2O2 30 % and solvent used for extraction. The efficiency of the best catalyst gives a maximum sulfur removal reaching 68.97%.